If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21(w + -937) = 630 Reorder the terms: 21(-937 + w) = 630 (-937 * 21 + w * 21) = 630 (-19677 + 21w) = 630 Solving -19677 + 21w = 630 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '19677' to each side of the equation. -19677 + 19677 + 21w = 630 + 19677 Combine like terms: -19677 + 19677 = 0 0 + 21w = 630 + 19677 21w = 630 + 19677 Combine like terms: 630 + 19677 = 20307 21w = 20307 Divide each side by '21'. w = 967 Simplifying w = 967
| 0=8+4x | | 7x-11=x+1 | | -47+5x=30-2x | | k-10/2=5 | | w-650=500000 | | 2.33*x=9 | | 4.8+v=14 | | (4z-7)(6+z)=0 | | x(32-6x)=0 | | (4z-7)(5+z)=0 | | x-32=-5(6x-6) | | 9(-4-p)=3(-4p-8) | | k-8=24 | | 4/17y-16=0 | | ax^2+bs+c=0 | | 7/4=9/r | | 6[5(3-9)-1]+2= | | 7x-2=5x-9 | | f(12)=.25(12-3) | | 8x-1=11x-9 | | 2-u=6 | | -5(1+6X)-8x=38+5x | | 4=2u-2 | | 4i/9-6i | | 0.5p=3.5 | | -x+17+3x+17=-4 | | 3+4y=9 | | 0.25w=16 | | -6k+3=-7-(6k-8) | | 2=2m-2 | | 4x(2x+9)-2(5x+6)= | | 7x+4-3+5-3x= |